Effect of different levels of synthetic astaxanthin on growth, skin color and lipid metabolism of commercial sized red porgy (Pagrus pagrus) - Nogueira, Natacha (2021)
A study was undertaken to evaluate the effects of supplementing commercial feeds with Car ophyll® Pink, a gelatin-encapsuled astaxanthin, on growth parameters, lipid composition, pigment concentration and skin color of commercial size red porgy. Three isonitrogenous diets were formulated containing different levels of astaxantin: Ctrl diet (no pigment added), A50 diet (with 50 mg/kg of astaxanthin) and A80 diet (with 80 mg/ kg of astaxanthin). Four groups of fish (386.29 ± 29.50 g initial weight) were grown in triplicate tanks (10 fish per tank). Ctrl, A50 and A80 groups were fed the respective diets to apparent satiation for 180 days, while a fourth group was fed A50 diet for 90 days followed by A80 diet for another 90 days (A50A80). At the end of trial muscle samples were collected for composition analysis, liver and mesenteric fat for lipid composition determination and skin samples for carotenoids quantification. Dietary astaxanthin supplementation had no effect on growth performance and hepatosomatic index. However, A50A80 group displayed a lower muscle protein content and higher fat content when compared to the other groups. There was no clear effect of dietary astaxanthin supplementation on the liver’s and mesenteric fatty acid profile. Although there was no significant effect on skin total carot enoids, the astaxanthin content tended to increase in fish fed astaxanthin supplemented diets, which was reflected on redness values. Accordingly, dietary astaxanthin supplementation (at 50 or 80 mg/kg for 6 months or at 50 mg/kg for 3 months followed by 80 mg/kg for 3 months) influenced positively skin hue and chroma of red porgy on both pectoral and caudal areas, improving the skin color in commercial sized red porgy and achieving hue and chroma values close to those previously reported for wild individuals. The results reported here provide evidence of the applicability of Carophyll® Pink to improve skin color of large size commercial red porgy, but further studies are needed to optimize this carotenoid supplementation in production farming.